Does per‐act HIV‐1 transmission risk through anal sex vary by gender? An updated systematic review and meta‐analysis. (2nd September 2018) - Baggaley, Rebecca F.; Owen, Branwen N.; Silhol, Romain; Elmes, Jocelyn; Anton, Peter; McGowan, Ian; van der Straten, Ariane; Shacklett, Barbara; Dang, Que; Swann, Edith M.; Bolton, Diane L.; Boily, Marie‐Claude
Abstract : Quantifying HIV‐1 transmission risk per‐act of anal intercourse (AI) is important for HIV‐1 prevention. We updated previous reviews by searching Medline and Embase to 02/2018. We derived pooled estimates of receptive AI (URAI) and insertive AI (UIAI) risk unprotected by condoms using random‐effects models. Subgroup analyses were conducted by gender, study design, and whether antiretroviral treatment (ART) had been introduced by the time of the study. Two new relevant studies were identified, one of which met inclusion criteria, adding three new cohorts and increasing number of individuals/partnerships included from 1869 to 14 277. Four studies, all from high‐income countries, were included. Pooled HIV‐1 risk was higher for URAI (1.25%, 95% CI 0.55%‐2.23%, N = 5, I 2  = 87%) than UIAI (0.17%, 95 % CI 0.09%‐0.26%, N = 3, I 2  = 0%). The sole heterosexual URAI estimate (3.38%, 95% CI 1.85%‐4.91%), from a study of 72 women published in a peer‐reviewed journal, was significantly higher than the men‐who‐have‐sex‐with‐men (MSM) pooled estimate (0.75%, 95% CI 0.56%‐0.98%, N = 4, P  < 0.0001) and higher than the only other heterosexual estimate identified (0.4%, 95% CI 0.08%‐2.0%, based on 59 women, excluded for being a pre‐2013 abstract). Pooled per‐act URAI risk varied by study design (retrospective‐partner studies: 2.56%, 95% CI 1.20%‐4.42%, N = 2 (one MSM, one heterosexual); prospective studies: 0.71%, 95% CI 0.51%‐0.93%, N = 3 MSM, P  < 0.0001). URAI risk was lower for studies conducted in the ART era (0.75%, 95% CI 0.52%‐1.03%) than pre‐ART (1.67%, 95% CI 0.44%‐3.67%) but not significantly so ( P  = 0.537). Prevention messages must emphasize that HIV‐1 infectiousness through AI remains high, even in the ART era. Further studies, particularly among heterosexual populations and in resource‐limited settings, are required to elucidate whether AI risk differs by gender, region and following population‐level ART scale‐up. Abstract : Forest plot of studies estimating per‐act HIV‐1 transmission probability through anal intercourse.